Analisis efisiensi dan efektivitas pelaksanaan tindakan tunggakan pajak terhadap penerimaan pajak badan Kantor Pelayanan Pajak Pratama Bitung 2021 - 2023 - Tampi, Kezia Akwila; Elim , Inggriani; Suwetja , I Gede (Riset Akuntansi dan Portofolio Investasi, 2025)
This study examines the efficiency and effectiveness of tax collection measures on corporate tax arrears at the Pratama Tax Service Office (KPP) Bitung during 2021–2023. Strengthening tax revenue is crucial for sustaining state finances, yet systematic evaluation of collection strategies remains limited. Using a qualitative descriptive approach, data were gathered through documentation and interviews with tax officials. The findings reveal that collection measures including seizure, account blocking, and auction, were implemented efficiently and effectively. Tax collection realization reached 91.9% of the target in 2021 (effective), 203.6% in 2022, and 125.8% in 2023 (very effective). These results indicate that the strategies employed not only improved compliance but also significantly enhanced corporate tax revenue. The study highlights the importance of sustained enforcement, inter-unit coordination, and the use of legal instruments to optimize tax arrears collection.